2013
DOI: 10.1007/s13197-013-1132-6
|View full text |Cite
|
Sign up to set email alerts
|

Screw pressing performance of whole and dehulled flaxseed and some physico-chemical characteristics of flaxseed oil

Abstract: Screw pressing performance of whole and dehulled flaxseed at different seed moisture (6.4 to 11.1 % d.b.) and press head temperature (80-120°C) was investigated. Oil recovery, residual oil, press rate and sediment content and some important physico-chemical characteristics were determined at six different levels (50, 60, 70, 80, 90 and 100 %) of dehulled flaxseed. Oil recovery decreased with increasing moisture content as well as press head temperature. Press rate was found maximum for 100 % dehulled flaxseed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 24 publications
5
29
1
3
Order By: Relevance
“…of pre‐treated whole flaxseed. Increased press rate at higher moisture content was also reported by Mridula et al () for dehulled and whole flaxseed sample. Similarly, Singh et al () reported decrease in press rate from 5.8 to 5.2 kg/h and 6.1 to 5.2 kg/h for cooked and uncooked crambe seeds with decrease in moisture content from 9.2 to 3.6% d.b.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…of pre‐treated whole flaxseed. Increased press rate at higher moisture content was also reported by Mridula et al () for dehulled and whole flaxseed sample. Similarly, Singh et al () reported decrease in press rate from 5.8 to 5.2 kg/h and 6.1 to 5.2 kg/h for cooked and uncooked crambe seeds with decrease in moisture content from 9.2 to 3.6% d.b.…”
Section: Resultssupporting
confidence: 81%
“…Though variable amount of sediments was observed in crude oil samples expelled following different press head temperatures but the variation was statistically insignificant (Table ). Contrary to this, Mridula et al () reported significant impact of press head temperature with minimum sediment content at 120°C with three studied temperature as 80–120°C. This variation in the findings in different studies may be due to the variation in the level of studied parameters and the crop properties.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Solvent extraction is the most efficient method and allows the recovery of over 98% of available oil. The disadvantages of this process are high costs and the necessity of using highly inflammable chemicals and possible solvent residues in the obtained oil [5]. Screw pressing is less expensive than solvent extraction because it requires only a mechanical power input instead of heat or organic solvents [6].…”
Section: Introductionmentioning
confidence: 99%